In vitro and In silico Studies of Kayu Raja (Cassia fistula L.) Leaves Extract as Potential Antifungal Agent Against Candida albicans - Tan David Christian; Kasiyati Kasiyati; Tri Yuliani; Ariyanti Saputri; Dadang Priyoatmojo; Marissa Angelina (Jurnal Kimia Sains dan Aplikasi, 2023)
Candida albicans is one of the most common fungal species causing opportunistic infections, such as candidiasis. Candida albicans has the ability to produce and secrete hydrolytic enzymes, namely secrete aspartate protease (SAP). SAP3 is a virulence factor for mucosal or disseminated infections. Cassia fistula leaves have bioactive compounds that can be used as antimicrobial agents, such as hyperoside, delphin, epicatechin, isoquercitrin, and astragalin. This study aims to determine the potential of bioactive compounds in Cassia fistula L. as an antifungal by in silico method molecular docking and Minimum Inhibitory Concentration (MIC) analysis with FE-SEM test for microscopical visual results. The results showed that the delphin compound had the best binding energy of -7.73 and an inhibition constant of 2.17 M, almost equivalent to ketoconazole as a positive control. MIC test of ethanol and ethyl acetate extracts of Cassia fistula leaves resulted in 100 ppm in the ethanol extract and 50 ppm in the ethyl acetate fraction. This result was supported by FE-SEM results, which showed that the ethanol extract at 100 ppm could damage the structure of Candida albicans colony.